2001
DOI: 10.1097/00002093-200104000-00008
|View full text |Cite
|
Sign up to set email alerts
|

The Disability Assessment for Dementia Scale: A 12-Month Study of Functional Ability in Mild to Moderate Severity Alzheimer Disease

Abstract: The Disability Assessment for Dementia (DAD) scale was developed and validated as a measure of functional ability in dementia. DAD results have been reported in Alzheimer disease (AD) randomized, controlled treatment trials of up to 6 months, but results beyond 6 months have yet to be described. SAB INT 12 was a randomized, double-blind, placebo-controlled, parallel-group study in mild to moderate AD that included DAD assessments at baseline, month 6, and month 12. One hundred forty-four patients with AD in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
84
1
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(96 citation statements)
references
References 10 publications
6
84
1
2
Order By: Relevance
“…In summary, previous studies have shown that individuals with greater global cognitive dysfunction at baseline experience a more rapid rate of decline in IADLs than individuals with milder impairment overall (Feldman et al, 2001;Schmeidler et al, 1998). The current results extend these findings to show that in particular, those patients with a greater degree of executive dysfunction at initial assessment tend to experience a more rapid decline in ratings of their functional status over time.…”
Section: Discussionsupporting
confidence: 82%
“…In summary, previous studies have shown that individuals with greater global cognitive dysfunction at baseline experience a more rapid rate of decline in IADLs than individuals with milder impairment overall (Feldman et al, 2001;Schmeidler et al, 1998). The current results extend these findings to show that in particular, those patients with a greater degree of executive dysfunction at initial assessment tend to experience a more rapid decline in ratings of their functional status over time.…”
Section: Discussionsupporting
confidence: 82%
“…4) (42). In comparison, after 12 months, untreated patients would be expected to deteriorate by 11 to 13 points on the DAD scale (17,60). The effect of galantamine in maintaining DAD scores at baseline levels provides important benefits in stabilizing patients with AD.…”
Section: Benefits Of Galantamine On Adlmentioning
confidence: 99%
“…A incapacidade nas AvD tem um grande impacto sobre a qualidade de vida dos pacientes e de seus cuidadores 7 , sendo um aspecto que prediz mais fortemente o uso de serviços de saúde e a institucionalização, mais do que outras medidas de gravidade 25 . Na amostra estudada, o questionário sensibilizou alguns cuidadores quanto a questões preservadas, permitindo orientações para o aumento da autonomia e qualidade de vida do paciente.…”
Section: Discussionunclassified
“…Além de avaliar a realização efetiva de atividades de lazer, a escala inclui questões sobre o interesse mostrado por elas. A DAD tem sido utilizada em ensaios clíni-cos, tendo sido capaz de evidenciar o efeito positivo de drogas sobre o desempenho funcional dos pacientes (manutenção ou melhora nas AvD após tratamento) [7][8][9][10][11][12][13][14][15][16][17] . considerando esses aspectos, realizamos a tradução e adaptação deste instrumento para a lín-gua portuguesa, verificando a confiabilidade interexaminadores e teste-reteste da versão traduzida e adaptada.…”
unclassified